Innovative shopping through mobile using Google’s ARCore - kumar P, Sathish; prakash S, Chandra; kumar K, Ajith; shri, M. Lawanya; K. Santhi; Mon, Feslin Anish (International Journal of Psychosocial Rehabilitation, 2020)
This paper is based on shopping through the augmented reality. By seeing the 3D virtual objects in the environment customer can buy the product and make decisions based on 3D virtual objects. It can increase the purchase rate of the customer. A new customer to the online shopping world can also easily trust and buy the products based on this augmented reality method.